Analysis of the system for zoning implementation of Quezon City, Philippines - Esteves, Catherine Joy P. (School of Urban and Regional Planning, University of the Philippines Diliman, 2016)
In Metro Manila, the system for zoning implementation plays a very crucial role in ensuring proper utilization of lands and its resources due to the increasing real estate activities at an unprecedented rate. The effectiveness of the said system should not only be limited to the compliance with what has been prescribed by certain guidelines but rather in terms of its responsiveness to the changing local conditions and the conformity of the actual land uses with the zoning policies set. This study analyzed the effectiveness of the system for zoning implementation of Quezon City, one of the LGUs in Metro manila, while coping up to the increasing demand for various land uses by the real estate market. By effectiveness, the system for zoning implementation was assessed and measured in terms of three (3) parameters: a) compliance with the requirements set by a certain guideline; b) responsiveness to the c hanging local conditions; and c) conformity of actual users with the approved Zoning Ordinance. Based on the data gathered through key informant interviews, field observations and documents reviews, Quezon City is not fully compliant with the requirements of the HLURB guidelines, particularly in terms of the required local structure and manpower. In terms of its responsiveness, Quezon City was able to establish those measures necessary to allow developments to take place, which were not permitted under the 2000 Zoning Ordinance, by virtue of granting amendments and deviations. When it comes to the conformity of actual land uses, taking the case of certain areas in Teacher's Village, the development of restaurants and cafes in the stretch of Maginhawa Street and its neighboring streets such as Magiting. Mapagkawanggawa and Malingap are not permitted under 2000 Zoning Ordinance.Thus, Quezon City's system for zoning implementation requires improvement and needs further strengthening especially in terms of its compliance with the existing guidelines and regular monitoring, review and evaluation of what is happening on the ground. Its responsiveness to the changing local conditions by providing supplemental development regulations and mitigating devices, however, is remarkable in response to the absence of an updated zoning ordinance.